Dataset on microstructural, structural and tribology characterization of TiC thin film on CpTi substrate grown by RF magnetron sputtering - Olayinka Oluwatosin Abegunde; Esther Titilayo Akinlabi; Philip Oluseyi Oladijo (Data in Brief, 2020)
The datasets in this article are supplementary to the corresponding research article [1, 2]. The planar morphology and topography of TiC thin films coated on commercially pure Titanium (CpTi) grown by RF magnetron sputtering were investigated using Field emission scanning electron microscope (FESEM) and Atomic force microscope (AFM). The mechanical properties such as Hardness and Young Modulus of the thin film coating was studied using Nanohardness. Furthermore, grazing incidence X-ray diffractometer (GIXRD) and Raman spectroscopy were used to analyse the structural and composition of the TiC thin film coating. Keywords: RF magnetron sputtering, TiC thin film, Field emission scanning electron microscope (FESEM), Atomic force microscope (AFM), Grazing incidence X-ray diffractometer (GIXRD), Raman spectroscopy, Nanohardness